Perspective of The Psychological Assessment Team on Factors Influencing Parental Acceptance of Students with Disabilities - Hevearita G. Rahayu; Hardi Warsono; Rina Kurniati; Hartuti Purnaweni (Psympathic : Jurnal Ilmiah Psikologi, 2023)
This study aimed to explore the perspective of the psychological assessment team on the factors influencing parental acceptance of students with disabilities. A qualitative design was used through a case study, with data gathered through in-depth interviews comprising four key participants, specifically two Psychologists and two Psychological Counsellors at Rumah Duta Revolusi Mental. The findings showed seven factors that either support or prevent parental acceptance of students with disabilities. The supporting elements include Knowledge, a Proactive and Open Attitude, Social Support, Financial Assistance and Capability, Availability of Facilities and Service Access, Experience, and Spirituality. Conversely, the preventing factors comprise Negative Stigma, Anxiety, Lack of Knowledge/Literacy, Maladaptive Beliefs, Negative Experience with Prior Services, Limited Financial Resources, and Limited Access and Infrastructure. Based on these findings, the study recommends that Semarang City should actively develop innovative policies to enhance parental acceptance of students with disabilities, addressing the identified factors comprehensively.